The Effect of Personal Vocabulary Notes Technique toward Students’ Vocabulary Achievement - Karimuddin, Karimuddin; Anisah, Lina (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
This research presented The Effect of Personal Vocabulary Notes Technique toward Students’ Vocabulary Achievement at the Second Grade of Pesantren Darul Istiqamah Amomotu. This research used quasi experimental design, divide into two groups: Experimental Class and Control Class. The researcher collected the data by giving pre-test in class to know students’ prior knowledge then giving treatment and post-test in which the researcher conducted teaching and learning process by Personal Vocabulary Notes Technique. The researcher use formula two-tailed test to analyze the result of the research whether there was an effect between students’ vocabulary after analyzing the data. The result of this research was an effect of PVN (Personal Vocabulary Notes) Technique toward Students’ Vocabulary Achievement at the Second Grade of Pesantren Darul Istiqamah Amomotu. It could be seen of the mean score post-test of the control class 66.07 was higher than the mean score post-test of the experimental class 77.86. The result showed that T-test > T-table 26.80 > 2.16. The alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. This study contributes to educational practices by examining a specific method (Personal Vocabulary Notes) that can enhance vocabulary learning. As it proven effective, this technique could be implemented more widely in classrooms to improve language acquisition.